STUDY OF FLOOD CONTROL IN LONGSTORAGE DEVELOPMENT IN BARITO KUALA DISTRICT - Nainggolan, Jandik
The Barito Kuala Regency longstorage development work was a proposal from the Barito Kuala Regency government which was carried out by the Kalimantan River Basin Office III. Longstorage Barito Kuala district has a flood storage volume of 408,000 m3, a normal storage volume of 362,400 m3, a normal inundation area of 91,200 m3, a high storage size of 340 m2. The main function of this long storage building is to control floods when there is a high intensity of rain. Floods often occur in the Barito Watershed (DAS) which are caused by high intensity rains and high tides. One of the government's efforts to deal with flood problems is to carry out longstorage development. This research was conducted to examine the function of long storage as a flood controller. The data collected for the research were primary data and secondary data which included topographical data, rainfall data, watershed characteristic data, climatological data, river water level data, river profile data, AWLR data, and sedimentation data. Hydrological analysis was carried out to determine the magnitude of the flood discharge that occurred. Hydraulics analysis was carried out to model the river in flood conditions. While the sedimentation analysis is carried out to determine the amount of sedimentation that enters the long storage.